Corporate Investment, Financial Structure and Debt Maturity: New Evidence from Saudi Arabia - Alnori, Faisal (International Journal of Economics and Financial Issues, 2024)
There are twofold objectives in this study. The first is to examine the role of financial leverage in explaining corporate investment decisions. The second aim is to investigate the impact of corporate debt maturity structure on corporate investment levels. The sample used consists of listed non-financial firms operating in Saudi Arabia over the years 2011-2022 and the method applied is the dynamic Generalised method of moments (GMM). In contrast to the prevailing inverse relationship between leverage and corporate investment, the present study finds that financial leverage increases Saudi-listed corporation investment which does not support the agency theory views that leverage restricts firms’ investment and does not accept the disciplinary role of leverage on firms’ managers. Further, the study finds no evidence that debt maturity structure impacts corporate investment decisions. It is concluded that financial leverage has more impact on corporate investment than debt maturity. Important implications are offered to corporate managers, investors, and lenders.